Pendampingan Optimalisasi Belajar Anak Usia Sekolah Dasar Melalui Bimbingan Belajar Di Dukuh Tengah Desa Nambangrejo Sukorejo - An Nadya, Saffina Muzdalifa; Khafidhoh, Khafidhoh (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of this assistance is to optimize the learning process for elementary school age students in Dukuh Tengah, Nambangrejo Sukorejo village. The method in this research uses the ABCD method approach to plan supporting activities. The ABCD approach has 5 key stages, namely Discovery; This stage involves identifying the assets owned by the Dukuh Tengah community. Dream (Dream); At the Dream stage, the community together formulates visions and dreams related to improving children's education. Design (Designing); The Design stage involves planning a tutoring program based on the assets and dreams that have been identified. Define (Determine); In the Define stage, the program that has been designed is tested through conducting experiments. and Destiny (Doing); Implementing plans that have been prepared and carrying out ongoing evaluations to ensure the success of the program. The process uses a descriptive qualitative method by describing the results with related theories. The target of this tutoring assistance is elementary school age students from grades 2 to grade 6 in the central hamlet of Nambangrejo village. The results obtained after this assistance are an increase in students' interest in learning, an increase in understanding of the subject matter, the creation of a conducive learning environment, an increase in parental involvement.